Pelleting and priming effect on biochemical parameters of fennel (Foeniculum vulgare) seeds - SINGH, SURYAPAL; SINGH, HARSHITA; MOR, V S (The Indian Journal of Agricultural Sciences, 2021)
The experiment was carried out to extrapolate the effect of seed pelleting and priming on biochemical traits of fresh and stored fennel (Foeniculum vulgare Mill.) seeds in the Laboratory of Department of Seed Science and Technology, CCS Haryana Agricultural University, Hisar during 2017-19 under ambient conditions on cultivar Hisar Swarup (HF 33). Results showed that the biochemical parameters, viz. catalase, peroxidase, dehydrogenase and superoxide dismutase decreased significantly as storage period increased in all the treatments. Prior to storage in case of seed pelleting, biochemical activity was recorded highest in seeds pelleted with Captan (3 g/kg) + Imidacloprid (2 g/kg), followed by neem leaf powder (100 g/kg seeds) and KNO3 (1.0%), except peroxidase activity. Whereas, in case of priming, maximum biochemical activity was observed in seeds primed with Trichoderma viride (8 g/kg seed), followed by KNO3 (1%), neem leaf extract (10%) and Trichoderma harzianum (8 g/kg seed). At the end of experiment, biochemical activity was highest in seeds pelleted with Captan (3 g/kg) + Imidacloprid (2 g/kg) after 18 months of storage followed by KNO3 (1%), except in peroxidase activity. In case of catalase and dehydrogenase activity, seed pelleting with neem leaf powder (100 g/kg seeds) showed at par value with Captan (3 g/kg) + Imidacloprid (2 g/kg).